Assessment of the treatment needs of community recovery Services in Spain: From the perspective of service users, families, and mental health professionals. (8th September 2022) - Vilamala, Sonia; Puig, Marta; Ochoa, Susana; Martín‐Martínez, Jose Ramón; Hernández, Ana; Balsera, Joaquin; Verdaguer‐Rodríguez, Marina; Villellas, Raul; Arenas, Otilia; García‐Franco, Mar
Abstract: Profile of Community Recovery Services users has changed over the years and has become more diverse. To explore the evolution of treatment needs, this study aimed to identify users' needs, from the point of view of different agents implicated in the recovery process. We explored the consistency between the agents using the focus group technique. We defined four groups ( n = 58): service users, family members, professionals, and referring professionals. We pre‐identified topics related to recovery, such as illness‐related losses, imaginary of CRS, expectations, activities, and life goals. All agents recognised losses related to the mental illness, the need for carrying activities out of the Community Recovery Services, and for including families in the recovery process. The groups differed in some areas, such as the identification of activities that should be encouraged, or the importance of promoting vital expectations. Our findings suggest that it is important to identify the needs of different agents involved in the recovery process. There is consistency in the service users' needs, but there are some differences that need to be considered. Interventions should be personalised, covering functional, cognitive, and relational losses related to the mental illness.